HUBUNGAN ANTARA DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN PROKRASTINASI MENGHAFAL AL-QUR’AN PADA SANTRI DI PONDOK PESANTREN MODERN ISLAM ASSALAAM SURAKARTA - Hermit Arsita Wiyarti; Imam Setyawan (Faculty of Psychology, Diponegoro University, 2017)
The process of memorizing Al-Qur’an often become a phase full of obstacles that cause stress. The delay in completing memorization of Al-Qur’an is called procrastination on memorizing Al-Qur’an, which is done to avoid stressful situations. Peer social support is one of the factors that can reduce the negative effects of stress so that the process of memorizing Al-Qur’an can run smoothly. This study aims to determine the relationship between peer social support with procrastination on memorizing Al-Qur’an among student at Modern Islamic Boarding School Assalaam Surakarta.The sample of research was 161 students of Modern Islamic Boarding School Assalaam Surakarta which was taken by using simple random sampling technique. The data were collected using two psychological scales, Procrastination on Memorizing Al-Qur’an Scale (35 valid items, α = 0,919) and Peer Social Support Scale (54 valid items, α = 0,969). Data analysis used statistical non parametric Spearman’s Rho to see the relationship between the two variables.The results of this study showed a coefficient correlation of -0,335 with a significance value of 0,000 (p<0,05). These results indicate that there is a negative and significant relation between peer social support with procrastination on memorizing Al-Qur’an among student in Modern Islamic Boarding School Assalaam Surakarta, which is mean hypothesis proposed by researcher is accepted. The higher peer social support is likely to lead to lower procrastination on memorizing Al-Qur’an. Conversely, the lower peer social support is likely to lead to higher procrastination on memorizing Al-Qur’an.